Marital Self-Regulation in Married Women based on Emotional Schemas and Behavioral Systems: With Emphasis on the Role of Mediating Social Exchange Style in Interpersonal relationships - Ofsiyehzadeh, Maryam; Farghadani, Azadeh; Shaterian Mohamadi, Fatemeh (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The aim of this study was to modeling marital self-regulation based on emotional schemas and behavioral systems with the mediating role of social exchange styles. Methods: This descriptive study was conducted using a correlational design. Statistical population was all married female students of Islamic Azad University, Karaj Branch, in the 2020-21 academic year of whom 420 students were selected using convenient sampling. They completed the Behavioral Self-Regulation for Effective Relationship Scale by Wilson et al. the Leahy’s Emotional Schema Scale, the Carver and White’s BIS/BAS scales and the Leybman’s Social Exchange Styles Questionnaire. Data were analyzed using structural equations and Amos software. Results: In addition to the significant direct effect of emotional schemas (adaptive and maladaptive) and behavioral activation on marital self-regulation, fairness and individualism played a positive mediating role between behavioral activation and adaptive emotional schemas in marital self-regulation. In addition, individualism played a negative mediating role between behavioral inhibition and maladaptive emotional schemas in marital self-regulation (P=0.05). Conclusions: In addition to the positive role of adaptive emotional schemas, behavioral activation and fairness style in marital self-regulation, the individualism style of social exchange had a different function in marital self-regulation of married women based on the type of emotional schemas and brain-behavioral systems and it could have a different effect on the cost/benefit estimation in relationships.